Efficacy of Endodontic Disinfection Protocols in an E. faecalis Biofilm Model—Using DAPI Staining and SEM - Maria Dede; Sabine Basche; Jörg Neunzehn; Martin Dannemann; Christian Hannig; Marie-Theres Kühne (Journal of Functional Biomaterials, 2023)
The aim of this study was to investigate the antimicrobial efficacy of different disinfection protocols in a novel Enterococcus faecalis biofilm model based on a visualization method and to evaluate the potential alteration of dentinal surface. A total of 120 extracted human premolars were allocated to 6 groups with different irrigation protocols. The assessment of the effectiveness of each protocol and the alteration of dentinal surface were visualized by using SEM and fluorescence microscopy (DAPI). A dense E. faecalis biofilm with a penetration depth of 289 μm (medial part of the root canal) and 93 μm (apical part) validated that the biofilm model had been successfully implemented. A significant difference between the 3% NaOCl groups and all the other groups in both observed parts of the root canal (p < 0.05) was detected. However, the SEM analysis revealed that the dentinal surface in the 3% NaOCl groups was severely altered. The established biofilm model and the visualization method based on DAPI are appropriate for bacterial quantification and evaluation of the depth effect of different disinfection protocols in the root canal system. The combination of 3% NaOCl with 20% EDTA or MTAD with PUI allows the decontamination of deeper dentine zones within the root canal but simultaneously alters the dentinal surface.